Sharing – transferring knowledge in companies - Radosavljević, Darko (Sociološki pregled, 2022)
Knowledge management is a manner in which an organization creates, maintains and shares knowledge. It constitutes an integral function of business operations in many companies that build their success by creating new knowledge, then distributing it within the organization and integrating it in new technologies and products. Understanding the idea of knowledge sharing appears as a key research area within a wide scope of research into transfer of technologies and innovations. The paper emphasizes the importance of knowledge and professionalism as key resources of enterprises and national economies. Moreover, it points to different types of knowledge and models of creating and using knowledge. By sharing – transferring knowledge, individual knowledge is transformed into organizational and contributes to improved performances of a company.